2019
DOI: 10.2106/jbjs.st.18.00106
|View full text |Cite
|
Sign up to set email alerts
|

Extensor Mechanism Reconstruction with Use of Marlex Mesh

Abstract: Background: Marlex mesh reconstruction of the extensor mechanism via a stepwise surgical approach is a viable option to treat disruption of the extensor mechanism after total knee arthroplasty (TKA). Description: Extensor mechanism reconstruction with mesh involves a stepwise surgical approach with a particular monofilament polypropylene mesh (Marlex; C.R. Bard). Prior to incision, the 10 3 14-in (25 3 36-cm) sheet of Marlex mesh is rolled onto itself 8 to 10 times and sewn together. If the tibia is not being … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 4 publications
0
11
0
Order By: Relevance
“…While several protocols are available for acute QTR rehabilitation, there is a lack of studies about rehabilitation and follow-up after treatment of chronic ruptures, ruptures after TKA, and re-ruptures. In this study, the mean period of immobilization reported was 5.7 weeks, even though Abdel et al and Nodzo et al, who performed tendon augmentation using synthetic mesh in patients with QTR after TKA, reported longer immobilization periods of respectively 12 and 8 weeks [ 37 , 38 ]. The choice of the best procedure is closely linked to the type of lesion.…”
Section: Discussionmentioning
confidence: 69%
See 4 more Smart Citations
“…While several protocols are available for acute QTR rehabilitation, there is a lack of studies about rehabilitation and follow-up after treatment of chronic ruptures, ruptures after TKA, and re-ruptures. In this study, the mean period of immobilization reported was 5.7 weeks, even though Abdel et al and Nodzo et al, who performed tendon augmentation using synthetic mesh in patients with QTR after TKA, reported longer immobilization periods of respectively 12 and 8 weeks [ 37 , 38 ]. The choice of the best procedure is closely linked to the type of lesion.…”
Section: Discussionmentioning
confidence: 69%
“…(2019) Shi et al 23 10 M 13 F 61 Fall from a standing height after TKA 21 days (range, 14 to 56 days) Complete quadriceps tendon rupture following TKA + 1rerupture Obesity, diabetes, chronic dialysis, steroid dependence (12pt) V-Y turndown flap 1 hematoma and delayed wound healing 1 fall and rerupture after 24 months [ 47 ] A simultaneous bilateral quadriceps and patellar tendons rupture in patients with chronic kidney disease undergoing long-term hemodialysis: a case report. (2020) Tao et al 2 M 33,5 1 fall down the stairs 1 sudden twist bilateral QT ruptures Chronic renal failure, with hemodialysis dependence for 9 and 11 years Krackow sutures None [ 37 ] Extensor Mechanism Reconstruction with Use of Marlex Mesh. (2019) Abdel et al 27 10 M 17 F 67 Rupture after TKA 219 days Complete QT rupture Obesity, diabetes, coronary artery diease, hypertension, OA, rheumatoid arthritis, Parkinson, cancer (leukemia, breast cancer, bladder cancer) Marlex Mesh augmentation 5 QT re-ruptures that required mesh revision [ 38 ] Polypropylene mesh augmentation for complete quadriceps rupture after total knee arthroplasty.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations